Turkish Television Drama in Pakistan: Effects on University Students - Hameed, Muhammad Basharat; Niaz, Babrak; Adnan, Malik (Journal of Peace, Development and Communication, 2020)
This study attempts to investigate the effects of Turkish drama on University students. Drama plays influential role in changing life style of its audience. Through drama viewers come to know the diverse values of different cultures and it has a different effect on different audience. University level students are more expose to media especially with television drama and current study is an attempt to gauge the effects of Turkish drama on youth. The students of Punjab University Lahore, GC University Faisalabad, University of Gujrat and The Islamia University of Bahawalpur are selected as respondents. The study is qualitative and quantitative in nature and non-probability sampling technique is used for data collection. Questionnaires were distributed in 400 respondents and hypotheses were also constituted to envisage the general perception. The data collected through questionnaire accepted two hypothesis while on of the hypothesis was rejected. The study finding states that Turkish dramas are good source of entertainment but these dramas are not challenging basic teachings of Islam and it has made no effects on our norms. On the basis of findings, suitable recommendations are suggested.